Do multi-sport athletes make better swimmers? - Stott, M. J. (Swimming World Magazine, 2018)
Do Multi-Sport Athletes Make Better Swimmers? While there is no scientific certainty surrounding this question, there is considerable empirical evidence to support it. We can learn more about the benefits of being a multi-sport athlete checking out the November 2018 issue of SW.